Efektifitas Program Bantuan Sosial Dalam Mengurangi Kemiskinan - Muh. Syata, Wahyu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Poverty is one of the main challenges faced by Indonesia, despite a decrease in poverty rates over the past few decades. The Indonesian government has implemented various social assistance programs such as the Family Hope Program (PKH), Direct Cash Assistance (BLT), and basic needs subsidy programs to reduce poverty. This research aims to analyze the effectiveness of social assistance programs in reducing poverty in society. The method used is a literature review utilizing relevant literature, such as books, journal articles, theses, and official documents. The research results show that social assistance programs are capable of increasing the purchasing power of the poor, fulfilling basic needs, providing health services, and education, as well as helping to break the intergenerational poverty cycle. However, the effectiveness of this program faces various challenges, such as misdirected distribution and the lack of awareness among beneficiaries to utilize the aid productively. To enhance the sustainability of social assistance programs, they need to be combined with economic empowerment initiatives that promote independence and skill development for beneficiaries. Improvements in targeting, transparency, and integration with economic development programs are necessary to create sustainable long-term solutions